2010
DOI: 10.4238/vol9-4gmr788
|View full text |Cite
|
Sign up to set email alerts
|

Prospecting candidate SNPs for backfat in Canchim beef cattle

Abstract: ABSTRACT. Canchim is a composite cattle breed developed in Brazil for beef production. One of the breeding objectives is to increase fat deposition. QTLs for fat thickness and/or marbling have been reported on BTA4 and BTA14. The IGFBP3 and DDEF1 genes, mapped to BTA4 and BTA14, respectively, affect adipogenesis. We looked for SNPs in the IGFBP3 and DDEF1 genes that could be associated with backfat thickness in Canchim beef cattle. For SNP identification, sires with the highest accuracy were ranked according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
(18 reference statements)
2
11
1
1
Order By: Relevance
“…We have to considerate that the SNP effect on trait variation could be biased by the small sample size analyzed, so including more animals in these analyses can help to confirm the results obtained here. Although this gene is located in a QTL for backfat thickness and had been associated with this trait in other studies (Veneroni et al, 2010), association between this SNP in ASAP1 gene and BFT was not confirmed in the Nelore population used in the present study. For REA a P-value near to the significance level (P≤ 0.01) after Bonferroni correction was observed.…”
contrasting
confidence: 72%
See 1 more Smart Citation
“…We have to considerate that the SNP effect on trait variation could be biased by the small sample size analyzed, so including more animals in these analyses can help to confirm the results obtained here. Although this gene is located in a QTL for backfat thickness and had been associated with this trait in other studies (Veneroni et al, 2010), association between this SNP in ASAP1 gene and BFT was not confirmed in the Nelore population used in the present study. For REA a P-value near to the significance level (P≤ 0.01) after Bonferroni correction was observed.…”
contrasting
confidence: 72%
“…The SNP in intron 13 of the ASAP1 gene was genotyped by an adapted ARMS methodology described by Veneroni et al (2010).…”
mentioning
confidence: 99%
“…In attempts to improve meat quality, previous studies have focused on the identification of candidate markers associated with meat quality traits, as well as backfat thickness, in Canchim and other Bos indicus × Bos taurus crosses in Brazil [20-24]. However, these have had limited success, particularly in response to markers on the DDEF1 and LEP genes [20,23].…”
Section: Introductionmentioning
confidence: 99%
“…The development and differentiation enhancing factor 1 gene (DDEF1) located at 9.7 Mb on BTA14 is related to adipogenesis (King et al, 1999). King et al (1999) purified and cloned the DDEF1 protein of bovine brain cells and observed that the expression of this protein resulted in the differentiation of fibroblasts in adipocytes in vitro and Veneroni et al (2010) found a effect (p ≤ 0.05) of allele substitution of an SNP in the DDEF1 gene on backfat thickness in Canchim cattle. Several works reported the existence of a QTL for backfat thickness in centromeric region of BTA14 (Moore et al, 2003;Casas et al, 2000) and the present study found association of this trait with the CSSM066 and ILSTS011 markers, but not with Tg5.…”
Section: Resultsmentioning
confidence: 99%